PEMANFAATAN APLIKASI WHATSAPP PADA PELATIHAN KERAJINAN KAIN FLANEL DALAM PEMBERDAYAAN MASYARAKAT DI BENING SAGULING FOUNDATION - Hudri, Iqsan; Nurhayati, Sri (IKIP Siliwangi, 2020)
Community Empowerment is essentially a planned social change strategy aimed at addressing problems or meeting the needs of the community. In the process of empowerment, people get learning to be able to independently make efforts to improve their quality of life. The purpose of this research is (1) to know how to use the Whatsapp application in flannel fabric training in Community empowerment in Bening Saguling Foundation, (2) Knowing the process of using the Whatsapp application in flannel fabric training in Community empowerment in Bening Saguling Foundation, (3) Knowing the results of the use of Whatsapp application in the training of flannel fabric in community This research was conducted at Bening Saguling Village Babakan Cianjur, district of Cihampelas West Bandung Regency. The respondents in this study were the managers of Bening Saguling Foundation, tutors and three representatives of the citizens learned. The methods used in this study are descriptive and qualitative approaches that are facts based on the outcome of the field. The result of this research is expected to facilitate the tutor to provide material outside the lesson hours, and help residents learn the community around Bening Saguling in terms of science, life skills, and also in terms of economics. Their skills increased as well as the well-being of his life made easy